2011
DOI: 10.1016/j.cmet.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid-Dependent Activation of Liver Estrogen Receptor Alpha Integrates Metabolic and Reproductive Functions via IGF-1

Abstract: Throughout evolution, organisms have devised strategies to limit fertility in case of prolonged starvation. In mammals, the liver plays a central role in the orchestration of mechanisms allowing for the maintenance of energy homeostasis. We here demonstrate that dietary amino acids regulate the transcriptional activity of hepatic estrogen receptor alpha (ERα) through an mTOR-dependent mechanism. As a result of ERα activation, hepatic IGF-1 mRNA and blood IGF-1 are increased. Conversely, calorie restriction or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 59 publications
(61 reference statements)
6
96
0
1
Order By: Relevance
“…To define tissue-specific contributions of estrogen signaling several groups have created hepatocyte-specific ERα-knock out mice to define the effects of estrogen signaling specifically through liver ERα. Della Torre and colleagues demonstrated a requirement for liver ERα in mediating amino acid regulation of the reproductive cycle (Della Torre et al 2011). Using a mouse model with ERα-deficiency in hepatocytes, we demonstrated that the ability of estrogens to reduce liver steatosis is lost in with deletion of liver ERα, suggesting that estrogens are acting directly in liver to reduce TG content through ERα (Palmisano et al 2016; Zhu et al 2013; Villa et al 2012).…”
Section: Estrogens and The Physiologic Regulation Of Liver Lipid Metamentioning
confidence: 99%
“…To define tissue-specific contributions of estrogen signaling several groups have created hepatocyte-specific ERα-knock out mice to define the effects of estrogen signaling specifically through liver ERα. Della Torre and colleagues demonstrated a requirement for liver ERα in mediating amino acid regulation of the reproductive cycle (Della Torre et al 2011). Using a mouse model with ERα-deficiency in hepatocytes, we demonstrated that the ability of estrogens to reduce liver steatosis is lost in with deletion of liver ERα, suggesting that estrogens are acting directly in liver to reduce TG content through ERα (Palmisano et al 2016; Zhu et al 2013; Villa et al 2012).…”
Section: Estrogens and The Physiologic Regulation Of Liver Lipid Metamentioning
confidence: 99%
“…In addition, studies in female mouse showed a specific synchrony of ER transcriptional activity in liver and reproductive tissues (Ciana et al, 2003;Della Torre et al, 2011a) with a rhythm imposed by the reproductive cycle. In this interplay, nutrient uptake was shown to be essential to maintain liver ER activity (Ciana et al, 2005;Della Torre et al, 2016;Della Torre et al, 2011b;Villa et al, 2012).…”
Section: The Mechanisms Subjecting Fertility To Nutrient Availabilitymentioning
confidence: 99%
“…This appears to be achieved by the fact that the hepatic ER requires both liganded and unliganded stimulation for its full transcriptional activation. The unliganded ER stimulation occurs in the presence of dietary AA (possibly through the IGF-1/AKT/mTORpathway) and, if AA intake is low, ER cannot be activated by the gonadal estrogens to the extent necessary for the synthesis of the molecules required for the progression of the reproductive cycle and, likely, for the maturation of the egg (IGF-1, cholesterol, lipids and the apolipoproteins necessary for their transport to the gonads) (Della Torre et al, 2016;Della Torre et al, 2011b). It is worth to underline that the synthesis of vitellogenins in mammalian liver is replaced by the synthesis of another member of the vitellogenin gene family, apolipoprotein B (ApoB), the primary apolipoprotein of VLDL, IDL and LDL (very-low, intermediate and low-density lipoprotein) particles (Packard et al, 2000).…”
Section: Consequences Of Placentation For Female Hepatic Metabolismmentioning
confidence: 99%
“…E2 can modulate GH actions on liver by acting centrally, by regulating GH secretion, and peripherally, modulating GH responsiveness. Importantly, the liver expresses ER which regulates development (Fisher et al, 1984), hepatic metabolic pathways (D'Eon et al, 2005;Ribas et al, 2010;Faulds et al, 2011), body growth (Vidal et al, 2000), protection from drug-induced toxicity (Yamamoto et al, 2006), hepatocarcinogenesis (Yager et al, 1994;Bigsby and Caperell-Grant, 2011), fertility (Della Torre et al, 2011), as well as lipid metabolism and insulin sensitivity (Simpson et al, 2005;Foryst-Ludwig and Kintscher, 2010).Thus, the liver is a sex steroid responsive organ and represents a site where critical interactions between estrogens and GH could be developed.…”
Section: Estrogens and Livermentioning
confidence: 99%
“…Particularly, E2 has been shown to induce Suppressor of Cytokine Signalling (SOCS)-2, a protein inhibitor for cytokine signalling, which in turn negatively regulate GHRJanus Kinase (JAK)-2-STAT5 pathway (Leung et al, 2004). Finally, the liver is a direct target of estrogens because it expresses ER (Heldring et al, 2007) which is connected with liver development (Fisher et al, 1984), regulation of hepatic metabolic pathways (D'Eon et al, 2005;Ribas et al, 2010;Faulds et al, 2011), growth (Vidal et al, 2000), protection from druginduced toxicity (Yamamoto et al, 2006), hepatocarcinogenesis (Bigsby and Caperell-Grant, 2011), fertility (Della Torre et al, 2011), as well as lipid metabolism and insulin sensitivity (Simpson et al, 2005;Foryst-Ludwig and Kintscher, 2010). Therefore, estrogen-GH interactions are relevant because physiological roles these hormones have in mammals, and the widespread use of estrogen and estrogen-related compounds in human.…”
mentioning
confidence: 99%